Distribution. N & E in Cricetidae - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
Distribution. N & E Europe (S Finland, Baltic states, Belarus, Ukraine, Moldova, and W & SW Russia), Balkans (E Romania, S Serbia, Macedonia, Bulgaria, and Greece), Turkey, Armenia, NW & N Iran, W & N Kazakhstan, and Russia as far E as Tobol River in W Siberia. Introduced to Svalbard and Jan Mayen Is in the N Atlantic and to several scattered localities in Siberia, Olkhon I in Lake Baikal, and Khabarovsk Krai in Russian Far East. Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 352, DOI: 10.5281/zenodo.6707142